2017
DOI: 10.1670/16-152
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Variation in the Cranial Osteology of Three Species of Endemic Australian Lizards (Ctenophorus: Squamata: Agamidae): Implications for the Fossil Record and Morphological Analyses made with Limited Sample Sizes

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…[32]); its role in supporting sensory structures, in food gathering, for social signalling and as a weapon, mean that it must be responsive to multiple selective pressures. Amphibolurinae includes some markedly varied and specialised skull shapes [33, 34], but apart from one recent limited study [35], there has been little examination of cranial growth patterns among different species.…”
Section: Introductionmentioning
confidence: 99%
“…[32]); its role in supporting sensory structures, in food gathering, for social signalling and as a weapon, mean that it must be responsive to multiple selective pressures. Amphibolurinae includes some markedly varied and specialised skull shapes [33, 34], but apart from one recent limited study [35], there has been little examination of cranial growth patterns among different species.…”
Section: Introductionmentioning
confidence: 99%
“…In part, that is because methods for integrating polymorphic characters into phylogenetic analyses are not straightforward. Nevertheless, continued investigations into morphological variation have yielded new insights into phylogenetic relationships and morphological evolution of squamates (e.g., Bhullar, 2011 ; Čerňanský, Smith & Klembara, 2014 ; Díaz-Fernández, Quinteros & Lobo, 2017 ; Stilson, Bell & Mead, 2017 ; Hernández Morales et al, 2019 ). Investigations into other vertebrate clades including turtles ( Joyce & Bell, 2004 ), frogs ( Bever, 2005 ), birds ( Kirchner-Smith, 2015 ), and mammals ( Gould, 2001 ) have also shown that substantial amounts of previously unreported morphological variation exist, some of which alter the diagnostic utility of previously reported features.…”
Section: Discussionmentioning
confidence: 99%
“…They have also developed many strategies for evading predators and catching prey, including speed (Cogger 2014), crypsis (Shoo et al 2008), defensive displays (Throckmorton et al 1985;Shine 1990), and spines (Pianka and Pianka 1970). They exhibit great variation in their skull anatomy (e.g., Siebenrock 1895;Bell et al 2009;Gray et al 2017;Stilson et al 2017;Gray et al 2019a, b). However, their potential to be defined as an "adaptive radiation" has not yet been explicitly investigated.…”
mentioning
confidence: 99%